Ushul Fiqh Syi’ah Imamiyah Tentang Nikah Mut’ah - Muhammad Ahmad Fulka Sa'dibih (Pena Islam Jurnal Pendidikan Agama Islam, 2020)
Legal products always depart from the method of determining the law called ushul fiqh. Although both are based on the Qur'an and Sunnah, but understanding and accepting the Qur'an and Sunnah are very likely to be different. This is due to differences in understanding of the texts and narration of a hadith. When a legal problem is understood in different ways, with different propositions, then it is likely that what arises later is a different legal product. An example is the mut‘ah marriage which by jumhur ulamas was declared a prohibited marriage, but by a group of Shi‘ah scholars it was permissible. Jumhur ulamas forbid mut'ah marriage based on the Qur'an and the hadith of the Prophet and the history of friends. Whereas the Shi'a group justifies the mut'a marriage also based on the Qur'an and the hadith of the Prophet.